2017
DOI: 10.1080/10641963.2016.1246562
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of CYP2C gene subfamily involved in epoxygenase pathway of arachidonic acids metabolism to hypertension susceptibility in Russian population

Abstract: Numerous studies demonstrated an importance of cytochrome P-450 epoxygenase pathway of arachidonic acids metabolism for the pathogenesis of essential hypertension (EH). The present study was designed to investigate whether common single-nucleotide polymorphisms (SNP) of CYP2C gene subfamily such as CYP2C8 (rs7909236 and rs1934953), CYP2C9 (rs9332242), and CYP2C19 (rs4244285) are associated with susceptibility to EH in Russian population. A total of 816 unrelated Russian individuals comprising 425 EH patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
8
0
10
Order By: Relevance
“…Through gene-pathway crosstalk analysis, we found that CYP family genes acted as important nodes connecting multiple pathways, including drug metabolism, oxidation reduction, arachidonic acid metabolism and retinol metabolism pathways ( Fig 1F). The importance of CYP genes in these pathways has been investigated previously in several studies (Polonikov et al, 2017;Ross & Zolfaghari, 2011;Danielson, 2002), and our finding was consistent with the published results.…”
Section: Transcriptome Changes During the Liver Injury Of Den-inducedsupporting
confidence: 93%
“…Through gene-pathway crosstalk analysis, we found that CYP family genes acted as important nodes connecting multiple pathways, including drug metabolism, oxidation reduction, arachidonic acid metabolism and retinol metabolism pathways ( Fig 1F). The importance of CYP genes in these pathways has been investigated previously in several studies (Polonikov et al, 2017;Ross & Zolfaghari, 2011;Danielson, 2002), and our finding was consistent with the published results.…”
Section: Transcriptome Changes During the Liver Injury Of Den-inducedsupporting
confidence: 93%
“…Polonikov и соавт. изучили возможную роль редких полиморфизмов CYP2C9 rs9332242 и CYP2C9 rs4918758 в развитии предрасположенности к ишемической болезни сердца (ИБС) [24] и эссенциальной гипертензии [25], однако результат был отрицательный.…”
Section: Cyp2c9unclassified
“…Результаты работ по редким аллелям гена CYP2C9 [24,25], а также генам VKORC1 [11,14,20] и GGCX [14] представлены в табл. 1.…”
Section: Cyp2c9unclassified
See 2 more Smart Citations